Seleção de genótipos e mapeamento de QTLs para resistência à murcha de fusário em feijão carioca - Cavalheiro, Sâmela Beutinger (2021)
Fusarium wilt, caused by the soil fungus Fusarium oxysporum f. sp. phaseoli, is a disease of great importance in the bean crop (Phaseolus vulgaris L.). Chemical control is not efficient and the use of resistant cultivars, within an integrated management strategy, is the most efficient way to control this disease. However, there is little information about the genetic control of the Fusarium wilt reaction and few carioca bean cultivars with satisfactory resistance level. Thus, three studies were carried out, with the objectives of: identifying parents and segregating populations of carioca beans with resistance to Fusarium wilt and other important characters; estimate genetic and phenotypic parameters and select carioca bean lines with resistance to fusarium wilt, high yield and mass of 100 grains and good visual appearance of grains; to study genetic control and identify molecular markers linked to QTLs that control the reaction to Fusarium wilt in the carioca bean cultivar BRS Notável. All evaluations were carried out in Santo Antônio de Goiás-GO, in the winter crop (sowing in May), in an area with high pathogen infestation, with central pivot irrigation. In the first study, 21 populations obtained from crosses in a complete diallel scheme between seven parents with grain carioca and some degree of resistance to Fusarium wilt were evaluated, together with two controls. Populations were evaluated in the F3, F4 and F5 generations, in 2012, 2013 and 2014, in a randomized block design, with three replications. The reaction to Fusarium wilt was evaluated using a grading scale, in addition to yield and mass of 100 grains. There were significant differences between populations for all traits evaluated. Additive and non-additive effects were important for Fusarium wilt reaction, yield and 100 grain mass. Cultivar BRS Notável was the most promising parent to participate in new crosses, presenting estimates of general combining ability (gi) different from zero, favoring the increase in resistance to fusarium wilt (-0.51), yield (87.90) and mass of 100 grains (0.23). The populations BRS Notável / CNFC 15872, BRS Ametista / BRS Notável, BRS Notável / BRSMG Talismã and BRS Ametista / BRSMG Talismã were the most promising for obtaining lines. In the second study, 114 lines obtained from BRS Notável / BRS Ametista and BRS Notável / CNFC 15872 populations, selected for their high resistance to Fusarium wilt, yield and mass of 100 grains, were evaluated. The 114 lines and seven controls were evaluated in experiments in triple lattice design 11 x 11, in the years 2015 and 2016, for reaction to Fusarium wilt and visual grain analysis, both using a grading scale, in addition to yield and 100 grain mass. Analysis of variance and genetic and phenotypic parameters were estimated. Genetic variability was detected among lines for the four characters. The high estimates of heritability, above 63%, and of expected gain with direct selection indicated the possibility of obtaining genetic gains for each character alone (23.0% for fusarium wilt reaction, 12.3% for yield, 9.6% for mass of 100 grains and 10.5% for visual appearance of grains). The simultaneous selection of 24 lines (21%) for the four characters showed gains of 12.9% for reaction to Fusarium wilt, 5.6% for yield, 3.4% for mass of 100 grains and 6.1% for visual aspect of grain. Three lines stood out (CNFC 19126, CNFC 19205 and CNFC 19131), being superior to BRS Notável for all characters. In the third study, the genotyping of SNPs and SilicoDArT markers was carried out using the DArTseq technology in the F2 generation of a mapping population obtained from the cross between the cultivars of Mesoamerican origin BRS Notável (resistant), of carioca grain, and BRS Supremo (susceptible), with black grains. Seventy-three progenies were evaluated for reaction to Fusarium wilt, by means of a grading scale, in the years/generations 2018/F2:4 and 2019/F2:5, together with the parents and five controls, in a block design at the random, with three repetitions. Analysis of variance and genetic and phenotypic parameters were estimated. A genetic map with 463 markers was obtained, with a total length of 1598.6 cM and average distance between markers of 3.5 cM. The analysis of phenotypic data showed variability between progenies and possibility of success with selection, with high estimates of genetic variance, heritability (90.6%) and expected gain with selection (28.5%), based on the joint analysis. Three QTLs were identified explaining between 25.1 and 50.4% of the phenotypic variation, all on chromosome 7, one in each of the evaluated years/generations (FOP7.2NS/ 2018 and FOP7.3NS/ 2019) and another based on in the joint analysis (FOP7.1NS). These three QTLs intersected between their intervals, with high stability in different years/generations. Therefore, the inheritance of the reaction in cultivar BRS Notável is quantitative, with the presence of some genes with greater effect. The additive effect for QTL FOP7.1NS was -1.24, indicating increased resistance in the presence of the BRS Notável parent allele. The SNP marker “SNP_Chr07_28294499_M12143”, present in all QTLs, explained 44.8% of the variation based on the pooled analysis. This marker is indicated to obtain probes for further validation.